AN ANALYSIS OF TRANSLATION STRATEGIES IN THE INDONESIAN TRANSLATION OF ENGLISH SONGS IN ANIMATED MUSICAL MOVIE ALADIN: A WHOLE NEW WORLD - Putri Dwi Gustiana; Ira Maisarah (Jurnal Bilingual, 2024)
The article reflect with songs lyrics as the data analysis. The data of this translation research was derived from a famous songs namely a whole new world (1992).This study aim at investigating of the translation strategies in the Indonesian translation of English song A whole new world in animated musical movie. According to the findings of this study, there are 35 verses in the song a whole new world. Based on the data in this research found that the most frequently used translation strategy is translation 18 times. As it can be seen in the tables and the least frequently used adaptation strategies.